Kemampuan Menulis Puisi Dengan Menggunakan Teknik Objek Langsung Kelas X SMA Negeri 1 Kabupaten Kepulawan Mentawai - Sindi Irawati; Najmi Hayati; Susanti Marisya (Kilau Publishing, 2023)
This study aims to describe the ability to write poetry using the direct object technique for class X SMA Negeri 1 Sipora, Kepulawan Mentawai Regency. There are three theories used in this study, namely (1) the meaning of writing, (2) the meaning of poetry (3) the direct object technique. This type of research is quantitative research using descriptive methods. The sampling technique used is random sampling. The data of this research is the score of the poetry writing test using the direct object technique for class X SMA Negeri 1 Sipora, Kepulawan Mentawai Regency. The data were analyzed based on the following steps: (1) examining the students' writing results (2) determining the score for the ability to write poetry using the direct object technique according to the assessment rubric. (3) Recording the scores obtained by students and converted into grades. (4) Determine the average value calculated for each aspect of the assessment. (5) describe the ability to write poetry using a scale of 10. (6) discuss the results of data analysis and make a histogram of the ability to write poetry as a whole. (7) conclude the results of data analysis. The results of this study indicate that (1) the ability of students to diction is with an average value of 84.52. (2) students' ability to image with an average value of 98.81. (3) students' ability to figure of speech with an average value of 76.19. Thus, the results of this study can be concluded that the ability to write poetry using the direct object technique for class X SMA Negeri 1 Sipora, Kepulawan Mentawai Regency obtained an average score of 86.50 which is in very good qualification (BS) because the average value ranges from 86- 95% on a scale of 10.